Classroom Technique Used in Teaching English Based on the Merdeka Curriculum - Yuta Febriansyah; Zakiyah Tasnim; Eka Wahjuningsih (EFL Education Journal, 2023)
The newest Merdeka Curriculum issued in 2021 began to be adopted by many high schools in Indonesia. However, not many studies were conducted on the technique used to teach English based on the curriculum. This descriptive case study aimed to investigate the technique used by an English teacher to teach English based on the Merdeka Curriculum as well as the teacher’s reasons for using the technique. The research data were collected through observations and interviews then the collected data were analyzed by using thematic analysis. The research found that the English teacher used the Presentation technique to teach English based on the Merdeka Curriculum. Furthermore, the teacher chose the technique because could help the students develop their speaking skills, and let them improving their communication skills.